Historiografi Hadis Prespektif Muhammad 'Ajjaj Al-Khatib Dalam Kitab Al-Sunnah Qabla Al-Tadwin - Siska Sukmawati (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2023)
The main point of this study discusses the historiography of hadith during the time of Rasulullah SAW according to the view of Muhammad 'Ajjāj al-Khatīb who focuses on the book al-Sunnah Qabla al-Tadwīn. This study is interesting to study because the history of hadith writing and its transmission during the time of Rasulullah SAW is still controversial today, and there are differences of opinion both among hadith scholars themselves and from orientalist circles. Therefore, in this study, the author chose to examine the views of a contemporary hadith scholar who had a life interval far from Rasulullah SAW. then this study has the aim of explaining historically the views of Muhammad 'Ajjāj al-Khatib on the history of hadith writing in the era of Rasulullah SAW. The method used in completing this research is qualitative, as well as a type of library research by collecting and analyzing primary data using a historical approach. The results obtained from this study indicate that 'Ajjāj al-Khatib assumes that there is no controversy between the traditions that prohibit and allow the writing of hadiths at the time of the Prophet, and both are not generaly so that all narrations are judged as authentic hadiths.